DEVELOPING MATERIALS FOR ACTIVE LEARNING OF GUIDED INQUIRY-INTEGRATED BOWLING CAMPUS ON THE TOPIC OF SENSE OF HEARING AND SONAR SYSTEM OF LIVING ORGANISM (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study is categorized as developmental research since it puts to its core the developing materials process for active learning of guided inquiry-integrated bowling campus. This research aims to construct adequate learning materials that are based on the criteria of validity, practicality, and effectiveness. The developed learning materials are lesson plan, teaching material, student worksheet, and posttest which were validated by experts to perceive information on materials’ validity and were tested to 25 eight graders of Junior High School on even semester of academic year 2015/2016 by using One-Group Pretest and Posttest Design. Data analysis was undertaken in quantitavely-qualitatively descriptive way resulting: 1) Valid categorized material validity (score 3.39); 2) Student worksheet legibility shows 100% for its interesting and understandable contents, 96% for its interesting appearance and its readable and adequate student book legibility for Junior High School students displaying the average sum of sentences the researcher took from sample text which was 5.69 sentences within 100 words under average sum of 145.8 syllables; 3) Very good execution rate (average score of 3.53); 4) Students responded very positively (98.58%); 5) Student centered learning activity; 6) Increase of students’ learning outcome (N-gain 0.88 and t = 23.04 t0.05;24 = 1.711 ). This research concludes that materials for active learning of guided inquiry-integrated bowling campus which were developed have been proved valid, practical, and effective to enhance learning outcome of Junior High School students.